Aligning Land Use with Land Potential: The Role of Integrated Agriculture. Issue 1 (1st April 2017) - Liebig, M. A.; Herrick, J. E.; Archer, D. W.; Dobrowolski, J.; Duiker, S. W.; Franzluebbers, A. J.; Hendrickson, J. R.; Mitchell, R.; Mohamed, A.; Russell, J.; Strickland, T. C.
Abstract : Core Ideas: Agricultural lands have varying potential based on climate, topography, and soils. Aligning land use and potential improves sustainable delivery of ecosystem services. Integrated agricultural systems (IAS) are uniquely adapted to variable land types. Socioeconomic barriers to IAS implementation are significant. Considerable research and education is needed to facilitate IAS adoption. Contemporary agricultural land use is dominated by an emphasis on provisioning services by applying energy‐intensive inputs through relatively uniform production systems across variable landscapes. This approach to agricultural land use is not sustainable. Achieving sustainable use of agricultural land should instead focus on the application of innovative management systems that provide multiple ecosystem services on lands with varying inherent qualities. Integrated agricultural systems (IAS) represent an alternative approach to prevailing land use, whereby site‐adapted enterprises are implemented to enhance synergistic resource transfer among enterprises and sustainable delivery of ecosystem services. Sustainable deployment of IAS on agricultural land involves placing the "right enterprise" at the "right intensity" at the "right time" on the "right location, " with the inherent attributes of location providing guidance for management decisions. There is an urgent need to design IAS that enhance delivery of ecosystem services while ensuring land potential thresholds are not exceeded.